Improving wear and corrosion resistances of Mg2Si/AZ91 composites via tailoring microstructure and intrinsic properties of Mg2Si induced by Sb modification - Peng Xiao; Yimin Gao; Yupeng Sheng; Cuicui Yang; Zhiwei Liu; Yanliang Yi; Wenyu Wu; Qiqiang Zhao; Manoj Gupta (Journal of Magnesium and Alloys)
To achieve simultaneous improvement in wear resistance and corrosion resistance, we propose a novel strategy to successfully develop Mg matrix composites containing blocky primary Mg2Si with small size instead of undesirable dendrite shape and large size. The tribological and corrosion behavior of Mg2Si/AZ91 unmodified and modified with 2.0wt.%Sb was subsequently and systematically investigated. The results show that Sb addition can significantly modify the morphology of primary Mg2Si to blocky polygon with smaller size of 12-25 µm, but has less effect on α-Mg grain size. Compared with unmodified composite, Sb modified Mg2Si/AZ91 composite has higher Brinell hardness and nearly unchanged microhardness of the matrix. Sb modified composite exhibits a 26% lower wear loss than unmodified composite, suggesting the greatly improved wear resistance. Microstructure analyses indicate that the main wear mechanism of composites is dominated by abrasive wear, and Sb addition can decrease the width and depth of grooves, resulting in a weakened abrasive wear behavior. Additionally, microcracks initiation on Sb modified Mg2Si particles can be restricted during the sliding friction process because of higher toughness and blocky polygonal shape induced by Sb doping, which is responsible for the improved wear resistance. Interestingly, Sb modified Mg2Si/AZ91 composite also demonstrates a superior corrosion resistance than unmodified composite due to the decrease of calculated corrosion rate from 1.57 mm/y to 0.74 mm/y, reduced by 52.8%. Such improvement is closely related to the reduced susceptibility to micro-galvanic corrosion, which is attributed to the reduced volta potential difference of Mg2Si relative to the Mg matrix, from 365 mV to 210 mV.